Acinetobacter spc.: A major isolates of nosocomial infection’s – clinical significance and antimicrobial susceptibility - Ghimire, G.; Magar, J.K.G.; Bhattacharya, S.; Mahapatra, T.M. (Journal of Institute of Medicine Nepal, 2007)
Acinetobacter spp. is ubiquitous, aerobic gram-negative coccobacilli that are now emerging as an important nosocomial pathogen. In our study over a period of one year (January 2002- December 2002) at BPKIHS, a tertiary care hospital, froma total no. of 1089 isolates frompus/ aspirates of ICU, Burns, Orthopedic and other post operative wards, 146 isolates (13.4%) were Acinetobacter spp. Out of 146, 23 isolates of Acinetobacter spp. were sensitive to base line drugs. Remaining 123 strains of Acinetobacter spp. were resistant to Cefotaxime (99.2%), Ceftazidime (98.4%), Tobramicin (95.9%), Amikacin (96.7%), Netilmicin (89.43%), Ciprofloxacin (96.7%).Apart fromthese antibiotics none of the strains were sensitive to Piperacillin. Journal of Institute of Medicine Vol.27(2) 2005